Four-wheel Steering Control Algorithm of Long Wheelbase Vehicles - ZHONG Hanwen; XIAO Lei; CHEN Wenguang; BU Jiling; LIU Biao (Kongzhi Yu Xinxi Jishu)
Long wheelbase design of vehicle can effectively increase the standing area without increasing the body length, thus increasing the passenger capacity. Today, with the development of urbanization, the long wheelbase vehicle design has become a trend, but this poses new challenges to the low-speed trafficability and high-speed stability of vehicles. This paper takes the long wheelbase commercial vehicle as the research object. Based on the vehicle dynamics and suspension design theory, the author first designed key parameters of long wheelbase vehicle and built an 18 degrees of freedom (DOF) dynamics simulation model for the vehicle; then designed the four-wheel steering (4WS) control algorithm according to the design parameters of the vehicle, for achieving the control target that the side slip angle tends to zero; and finally researched the influence of front-wheel steering (FWS) control and four-wheel steering control on the dynamic performance of the vehicle under the steady-state circumferential conditions with different turning radiuses and steering wheel angle pulse conditions with different speeds. The simulation results show that, under the steady-state circumferential turning condition with a low-speed turning radius of R15, the four-wheel steering design reduces the passing space from 4.6 m to 3.9 m, effectively improving the tracking ability of the front and rear axles of the vehicle and enhancing the trafficability and safety of the vehicle, and under the pulse condition with a maximum speed of 100 km/h, reduces the peak lateral acceleration from 4 m/s2 to 1.5 m/s2 and the peak yaw rate from 11°/s to 3°/s. Therefore, under high-speed steering wheel angle pulse conditions, the four-wheel steering design can effectively reduce the dynamic indicators of the vehicle, such as side slip angle, lateral acceleration and yaw rate, and improve the safety, stability and comfort of the vehicle at high speed.